Analisis Kelayakan Finansial dan Non Finansial pada Usaha Kopra di Desa Siduwonge Kecamatan Randangan Kabupaten Pohuwato - Yuriko Boekoesoe; Amelia Murtisari; Yenni Umar (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2015)
The purpose of this study were: 1). To determine whether the copra business financially   worth  the  effort  in  the  Village  District  of  Randangan  Siduwonge Pohuwato. 2). To determine whether the effort is worth the effort copra nonfinancial Siduwonge Village District of Randangan  Pohuwato. This study was conducted in May to July. This type of research is survey research. The data obtained in this study is that the data in the form of primary and secondary data. Sampling will  be done against  the  30  respondents  using  purposive  sampling.  The  analysis  used  is  the financial  analysis of the Net Present Value (NPV), Internal Rate of Return (IRR), Gross B / C Ratio, Net B / C Ratio and Payback Period. The results showed 1). Financially copra business in the Village District of Randangan  Pohuwato  Siduwonge  worth  the  effort  with  9.2  Million  NPV,  IRR (20.11%), Gross B / C ratio (1.27), Net B / C ratio (3.38 ) and payback period of 7 years  6  months.  2).  In  non-financial  businesses  in  the  village  copra  Siduwonge District of Randangan Pohuwato divided on several aspects which are as follows: a). Aspects  of  the  Market.  In  a  marketing  system  for  businesses   in  the  Village Siduwonge   copra,   farmers   sell   directly   to   buyers   who   typically   have   long subscription. Where the buyer directly come to the farmers who sell the copra. b). Technical  Aspects. In this technical aspect of the farmers in the village siduwonge almost all have their own land as many as 25 people, but there are also some who rent land that is 5 people. c). Management  aspects. In the management aspect of the planning is done before the process of harvesting coconuts into copra to be produced, the farmers in the village siduwonge not incorporated in the organization and for the direction and supervision in accordance with the land held by the copra farmers and for supervision also aims to work performed by farm workers in accordance with a predetermined agreement.